PERANCANGAN DAN PEMBANGUNAN PLATFORM DIGITAL BERBASIS E-MARKETPLACE PADA PENGELOLAAN PRODUK KOPI DI KABUPATEN SEMARANG - Dina Yeni Martia; Kenneth Pinandhito; Budi Prasetya; Suharmanto Suharmanto (Jurnal Riset Akuntansi Politala, 2023)
The development of information technology has brought a new era to the digital-based creative economy. The increasing needs of the community supported by the advancement of internet services used for various purposes, one of which is for business and trade purposes. One of the uses of the internet for business and trade purposes is using different existing marketing media, such as marketplaces. The Coffee Farmers Group in Kab. Semarang still markets its products by selling them directly to intermediaries or placing them in the nearest stalls. So, the marketing of coffee products is still limited to locals, and few people know. Based on the existing problems, building a marketplace-Based Digital Platform system is necessary to expand the marketing reach of MSME products for the Coffee Farmer Group. This study used an observation and interview approach. This research aims to build a digital-based marketing information system to expand sales further.